Exploring purchasing managers' influence tactics towards their internal clients: the case of non-production related items. Issue 4 (2nd October 2021) - Moncef, Btissam; Philipp, Bernd
ABSTRACT: By focusing on the interface between purchasing managers and internal customers, this research aims at understanding what types of influence tactics purchasing managers use to gain internal client commitment. Using a multiple case study methodology and data from 14 companies, the results show how purchasing managers work within the constraints of their organisational settings, but still manage to make their own choices and create their own spaces in which to do their jobs. The authors identified a set of influence tactics for how to deal with complexity and found soft tactics moderate daily practices and interactions between purchasing managers and internal clients. As opposed to other works, the authors explicitly adopted the perspective of purchasing managers.